Identification of galanin and its receptor GalR1 as novel determinants of resistance to chemotherapy and potential biomarkers in colorectal cancer - Stevenson, Leanne (2012)
PURPOSE: A major factor limiting the effective clinical management of colorectal cancer (CRC) is resistance to chemotherapy. Therefore, the identification of novel, therapeutically targetable mediators of resistance is vital. EXPERIMENTAL DESIGN: We used a CRC disease-focused microarray platform to transcriptionally profile chemotherapy-responsive and non-responsive pre-treatment metastatic CRC liver biopsies and in vitro samples, both sensitive and resistant to clinically relevant chemotherapeutic drugs (5-FU and oxaliplatin). Pathway and gene set enrichment analyses (GSEA) identified candidate genes within key pathways mediating drug resistance. Functional RNAi screening identified regulators of drug resistance. RESULTS: MAPK signalling, focal adhesion, cell cycle, insulin signalling and apoptosis were identified as key pathways involved in mediating drug resistance. The G-protein coupled receptor galanin receptor 1 (GalR1) was identified as a novel regulator of drug resistance. Notably, silencing either GalR1 or its ligand galanin, induced apoptosis in drug-sensitive and resistant cell lines and synergistically enhanced the effects of chemotherapy. Mechanistically, GalR1/galanin silencing resulted in down-regulation of the endogenous caspase 8 inhibitor FLIP(L), resulting in induction of caspase 8-dependent apoptosis. Galanin mRNA was found to be overexpressed in colorectal tumours, and importantly, high galanin expression correlated with poor disease-free survival of early stage CRC patients. CONCLUSION: This study demonstrates the power of systems biology approaches to identify key pathways and genes that are functionally involved in mediating chemotherapy resistance. Moreover, we have identified a novel role for the GalR1/galanin receptor-ligand axis in chemo-resistance, providing evidence to support its further evaluation as a potential therapeutic target and biomarker in CRC.